Spread of Chilean needle grass (Nassella neesiana) in Marlborough New Zealand - Bell, M. (New Zealand Plant Protection, 2006)
Chilean needle grass (Nassella neesiana) is a containment pest in the Regional Pest Management Strategy for Marlborough It is of concern because it has sharptipped seeds that bore into the eyes and pelts of livestock Discovered in Marlborough in the 1930s it now infests 4311 ha In 1987 18 properties were infested increasing to 53 by 2000 and 96 by December 2005 In addition both the range and density of Chilean needle grass has increased significantly since 1987 and to date no infestations have been eradicated Failure to stop this spread is due to the difficulty of both identification and control Effective control and land management methods for this weed are urgently needed The probability of this weed spreading further both within and beyond Marlborough appears to be high This conclusion along with land use changes has implications for the review of the Regional Pest Management Plan